La apropiación de la Pedagogía Pestalozziana en Colombia, 1845-1930 - Saldarriaga Vélez, Oscar (Pontificia Universidad Javeriana, 2014)
This article studies the introduction of modern pedagogy in Colombia from 1845 until 1930. It demonstrates that even prior to the boom of the Active School around 1935, the school was already experiencing reform and the professors were shaped in the name of modern thought. While exploring this phenomenon, the author sheds light on a series of paradoxes about knowledge and politcs that iluminate aspects seldom studied before in the history of the ethical and cultural modernization in Colombia.